Effects of Disking Versus Feed Patch Management on Northern Bobwhite Brood Habitat and Hunting Success - Leonard A. Brennan; Jeffrey M. Lee; Eric L. Staller; Shane D. Wellendorf; R. Shane Fuller (National Quail Symposium Proceedings, 2017)
More than 60 years ago, Herbert Stoddard (1931:376) wrote "there is little doubt that such methods [i.e., disking and harrowing] are more practical for Southeastern quail preserves than artificial plantings, which are costly on a large scale and not always effective." Incredibly, this statement, and testing it as an hypothesis, has been ignored by the bobwhite research community until the past 10 years. Therefore, we designed a pilot study to compare measures of northern bobwhite (Colinus virginianus) brood habitat (vegetation composition and arthropod biomass) and direct measures of hunting success (covey finds per half-day hunt) to test whether feed patches were really necessary for bobwhite habitat management in southern Georgia and northern Florida. We applied experimental treatments (disk only versus feed patch planting) by using shooting courses (150-250 ha each) on 2 southeastern shooting plantations during 1994, 1995 and 1996. Overall, results were equivocal between the feed patch and disking treatments; no consistent pattern or difference in brood habitat composition or hunting success was observed. One factor responsible for this pattern may be the relatively fine-grained scale (only 1-3% of the shooting courses were planted or disked) at which treatments were applied were insufficient to significantly influence bobwhite abundance. Further research using increased amounts of ground disturbance and planting (5%, 10%, 20%, etc.) will be required before the actual need for agricultural plantings can be determined in the context of their efficacy for bobwhite management. One potential result of these findings is that significant cost savings can be realized by disking rather than planting agricultural crop plants because at least 70% of the costs of planting are a function of seed, fertilizer and cultivation, whereas only about 30% are attributed to disking.